Efficient Catalyst-Free One-Pot Three-Component Synthesis of Novel Spirooxindole Derivatives, and Their Cytotoxic Activities - Han, Chao; Zhang, Tao; Zhang, Anqi; Wang, Dandan; Shi, Weimin; Tao, Jingchao (Synthesis, 2014)
A simple and efficient one-pot approach for assembling novel spiro[indolepyranopyrrole] derivatives was developed and used to prepare a series of biologically important compounds. The reaction was easily performed with high efficiency under very simple and mild conditions without any catalysts and it gave good yields, avoiding time-consuming costly synthesis and laborious workup and purification of products. The cytotoxic activities of these new spiro[indolepyranopyrrole] derivatives were evaluated in vitro. Most of the tested compounds exhibited significant cytotoxicities to Raji cell lines.
Keywords: polycyclic compounds; heterocyclic compounds; spiro compounds; multicomponent reactions; cytotoxins